2020
DOI: 10.3389/fnins.2020.00704
|View full text |Cite
|
Sign up to set email alerts
|

Gender Comparison of Psychological Comorbidities in Tinnitus Patients – Results of a Cross-Sectional Study

Abstract: Background: In the last decades, research focused on gender-related features in patients with tinnitus has often led to controversial results. The complex clinical picture of tinnitus patients often consists of an interdependent relationship between audiological symptoms and co-occurrent psychological disorders, which can complicate the diagnostic evaluation. Methods: Therefore, we studied 107 patients with tinnitus, investigating their psychological comorbidities in the light of gender differences. All patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 60 publications
2
16
0
Order By: Relevance
“…Overall, available evidence suggests that women tend to report higher HRQoL impairments in the context of psychological [38][39][40] or medical difficulties [41,42]. For chronic tinnitus, similar patterns emerged with women describing higher levels of emotional tension, psychological distress, and functional impairment [43][44][45][46], although these findings remain inconclusive [47,48]. To date, investigations on genderspecific differences in HRQoL for patients with chronic tinnitus are sparse.…”
Section: Introductionmentioning
confidence: 97%
“…Overall, available evidence suggests that women tend to report higher HRQoL impairments in the context of psychological [38][39][40] or medical difficulties [41,42]. For chronic tinnitus, similar patterns emerged with women describing higher levels of emotional tension, psychological distress, and functional impairment [43][44][45][46], although these findings remain inconclusive [47,48]. To date, investigations on genderspecific differences in HRQoL for patients with chronic tinnitus are sparse.…”
Section: Introductionmentioning
confidence: 97%
“…The tinnitus distress was assessed by using different multi-item questionnaires as listed as follows: The THI was used in 20 out of 33 studies ( 42 , 52 54 , 56 , 58 , 60 66 , 68 70 , 74 ), TFI by seven ( 45 , 46 , 50 , 52 , 55 , 57 , 68 ), TQ by five ( 44 , 48 , 51 , 56 , 73 ), TRQ by two ( 49 , 71 ), mini-TQ by two ( 59 , 72 ), and both THQ ( 66 ) and TPFQ by one study ( 66 ). The depressive symptoms were also assessed by using different multi-item questionnaires.…”
Section: Resultsmentioning
confidence: 99%
“…The ascertainment of exposure was of good quality in these studies due to the use of the predefined TQs. The representativeness of the exposed cohort in the other four studies [Meric et al ( 49 ), Shin et al ( 66 ), Fioretti et al ( 54 ), and Wang et al ( 55 )] was also judged to be of poor quality because of other reasons. Meric et al ( 49 ) did not report about where the cohort was recruited from.…”
Section: Resultsmentioning
confidence: 99%
“…Stress [35,36], depression, and anxiety [35,37,38] have been widely related to tinnitus. In our study, one third of the individuals reported anxiety in the online survey and a quarter in the outpatient cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also described a higher frequency of hyperacusis in patients with tinnitus than individuals without tinnitus. It is well known that tinnitus is particularly common in patients with hyperacusis, and they can co-occur in patients with severe tinnitus [35,45]. In addition, both conditions are widely associated and could share a common pathophysiology [46].…”
Section: Discussionmentioning
confidence: 99%